2006
DOI: 10.1073/pnas.0604521103
|View full text |Cite
|
Sign up to set email alerts
|

PlyC: A multimeric bacteriophage lysin

Abstract: Lysins are murein hydrolases produced by bacteriophage that act on the bacterial host cell wall to release progeny phage. When added extrinsically in their purified form, these enzymes produce total lysis of susceptible Gram-positive bacteria within seconds, suggesting a unique antimicrobial strategy. All known Grampositive lysins are produced as a single polypeptide containing a catalytic activity domain, which cleaves one of the four major peptidoglycan bonds, and a cell-wall-binding domain, which may bind a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
193
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 192 publications
(195 citation statements)
references
References 28 publications
2
193
0
Order By: Relevance
“…42 The two proteins are transcribed from two genes located in a single operon and separated by an intron-like sequence. 38,42 Furthermore, introns are rare in endolysin genes, but other exceptions do exist. 25 Engineering novel endolysin constructs The modular structure of endolysins provides an opportunity to engineer enzymes with altered bacteriolytic activity.…”
Section: Endolysins -Peptidoglycan Degrading Enzymesmentioning
confidence: 99%
See 1 more Smart Citation
“…42 The two proteins are transcribed from two genes located in a single operon and separated by an intron-like sequence. 38,42 Furthermore, introns are rare in endolysin genes, but other exceptions do exist. 25 Engineering novel endolysin constructs The modular structure of endolysins provides an opportunity to engineer enzymes with altered bacteriolytic activity.…”
Section: Endolysins -Peptidoglycan Degrading Enzymesmentioning
confidence: 99%
“…36,37 Endolysins with an intact CBD can also have a broad host range, such as with the streptococcal phage endolysin PlyC, which lyses several streptococcal species. 38 Even more promiscuous is the enterococcus phage f1 endolysin PlyV12, which lyses E. faecalis and several streptococcal and staphylococcal species. 39 Uniquely, the Bacillus phage endolysin PlyG lyses both vegetative cells and germinating spores of B. anthracis.…”
Section: Endolysins -Peptidoglycan Degrading Enzymesmentioning
confidence: 99%
“…Previous research spanning over 50 y has shown that PlyC can rapidly lyse cultures of groups A, C, and E streptococci in addition to Streptococcus uberis and Streptococcus equi and has been shown to protect mice from streptococcal challenge (12,13). PlyC is furthermore unique among the Gram-positive lysins in that it consists of two separate proteins-a single 50-kDa PlyCA subunit that is suggested to form a complex with at least eight 8-kDa PlyCB subunits (14). The two proteins are transcribed from two genes located in a single operon (14).…”
mentioning
confidence: 99%
“…PlyC is furthermore unique among the Gram-positive lysins in that it consists of two separate proteins-a single 50-kDa PlyCA subunit that is suggested to form a complex with at least eight 8-kDa PlyCB subunits (14). The two proteins are transcribed from two genes located in a single operon (14). PlyCA is known to contain an active cysteine, histidine-dependent amidohydrolases/peptidase (CHAP) domain, a fold distantly related to the papain-like cysteineprotease family, with Cys 333 and His 420 shown to be essential for amidase catalytic activity (14).…”
mentioning
confidence: 99%
“…A. Pohane and V. Jain Interestingly, however, most of the bacterial autolysins do not display peptidoglycan-binding specificity (Steen et al, 2003;Nelson et al, 2006;Fischetti, 2008). The G + phage endolysins have a very narrow range of substrate specificity, i.e.…”
Section: Regulation By Specificitymentioning
confidence: 99%